Effects of dexamethasone and IGF-1 on post-traumatic osteoarthritis-like catabolic changes in a human cartilage-bone-synovium microphysiological system in space and ground control tissues on earth - Dwivedi, Garima; Flaman, Lisa; Alaybeyoglu, Begum; Frank, Eliot H.; Black, Rebecca M.; Fite, Jordan; Scherzer, Chris; Barton, Ken; Luyster, Elizabeth; Thomas, Nathan; Boland, Eugene; Krishnan, Yamini; et al. (Frontiers in Space Technologies, 2024)
Post-traumatic Osteoarthritis (PTOA) results from traumatic joint injuries (such as an ACL rupture). Mechanical impact and an immediate synovial inflammatory response can result in joint tissue degradation and longer-term progression to PTOA. Astronauts are susceptible to increased exercise-related joint injuries leading to altered musculoskeletal physiology, further escalated due to microgravity and increased exposure to ionizing radiation. We applied a human Cartilage-Bone-Synovium (CBS) coculture model to test the potential of low-dose dexamethasone (Dex) and IGF-1 in ameliorating PTOA-like degeneration on Earth and the International Space Station-National Laboratory (ISS-NL, ISS for short). CBS cocultures were established using osteochondral plugs (CB) subjected to compressive impact injury (INJ) followed by coculture with synovium (S) explants. Study groups consisted of control (CB); disease [CBS+INJ]; treatment [CBS+INJ+Dex+IGF-1]; and drug-safety [CB+Dex+IGF-1].Outcome measures included cell viability, altered matrix glycosaminoglycans (GAG) and collagens, multiplex-ELISA quantification of released cytokines, histopathology, and metabolomic and proteomic analyses of spent media. A 21-day study on ISS-NL explored PTOA-like pathogenesis and treatment in microgravity. Tissue cards for study groups were cultured in custom-built culture chambers within multi-use variable-g platforms (MVPs). A marked upregulation in the release of inflammatory cytokines and tissue-GAG loss was observed in CBS+INJ groups in space and ground controls utilizing tissues from the same donors, similar to that reported in a previous multi-donor study on Earth; these changes were partly ameliorated by Dex+IGF-1, but with donor variability. Metabolomic and proteomic analyses revealed an array of distinct differences between metabolites/proteins released to the medium in Space versus on Earth.